Neutrophil to Lymphocyte Ratio within Clinical Staging of Head and Neck Squamous Cell Carcinoma - Orlena Dharmantary Kartika; Bambang Purwanto; Yussy Afriani Dewi (Althea Medical Journal, 2019)
Background: Neutrophil to lymphocyte ratio (NLR) is one of the inflammatory markers, associated with malignancies progression and metastasis, including head and neck squamous cell carcinoma (HNSCC). Neutrophil to lymphocyte ratio is presenting the activity index of protumor and antitumor. It is easy to perform in daily clinical practice, obtained from blood examination. The aim of this study was to assess the prognostic value of NLR in HNSCC patients, associated with the clinical staging.Methods: This study was an analytic design to explore the relationship between NLR and clinical staging. The sample was collected from pre-treatment HNSCC patients who came to the Head and Neck Oncology Clinic, Dr.Hasan Sadikin General Hospital. The data consisted of disease history, ENT examination, staging determination, and blood sample examination for NLR count.Results: In total, data on 92 HNSCC patients were collected. There was a statistically significant association between NLR with clinical staging in HNSCC (p<0.001). The higher the NLR, the higher the clinical stage, whereas the lower the NLR, (OR14.1; 95% CI 3.4–59.0).Conclusions: There is a significant association between NLR with clinical staging in HNSCC. Further study is needed to explore NLR as a prognostic marker in HNSCC patients